2021
DOI: 10.3389/fpsyt.2021.703609
|View full text |Cite
|
Sign up to set email alerts
|

Urgency in Improving Child Health Care Workers' Awareness and Knowledge of ASD: Findings From a Cross-Sectional Study in Southwest China

Abstract: Objective: To evaluate the levels of awareness and knowledge of ASD among child health care workers in China, we conducted a cross-sectional, questionnaire-based study to assess the participants' awareness and knowledge of ASD.Methods: A total of 159 child health care workers from Southwest China participated in the survey and filled out the questionnaire.Descriptive analysis was conducted on the five parts of the questionnaire, including general knowledge, symptomology, screening and diagnosis, and interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Using the KCAHW questionnaire, the mean score for the study population was 13.38 ± 4.48 points, which suggested that there is a need to improve the ASD knowledge in Chinese pediatric residents. Our results were in sync with a previous study which evaluated ASD awareness and knowledge in child health care workers in Southwest China [ 28 ]. Pediatric residents or pediatricians in different countries had different levels of ASD knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Using the KCAHW questionnaire, the mean score for the study population was 13.38 ± 4.48 points, which suggested that there is a need to improve the ASD knowledge in Chinese pediatric residents. Our results were in sync with a previous study which evaluated ASD awareness and knowledge in child health care workers in Southwest China [ 28 ]. Pediatric residents or pediatricians in different countries had different levels of ASD knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Using the KCAHW questionnaire, the mean score for the study population was 13.38 ± 4.48 points, which suggested that there is a need to improve the ASD knowledge in Chinese pediatric residents. Our results were in sync with a previous study which evaluated ASD awareness and knowledge in child health care workers in Southwest China [27]. Pediatric residents or pediatricians in different countries had different levels of ASD knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Guizhou province is located in Southwest China, which is an underdeveloped region in terms of medical resources and economic level. Early screening of ASD is limited, and our previous research found low levels of awareness and knowledge of ASD among child health care workers in Guizhou province (14). Thus, there is an urgent need to establish the early screening network of ASD in these less developed areas, in China.…”
Section: Intervention Status Of Autism Spectrum Disordermentioning
confidence: 96%
“…Medical resources and economic levels are uneven in China ( 13 ), and Beijing and Changsha are developed cities. Our previous research found low levels of awareness and knowledge of ASD among child health care workers in Guizhou province in China ( 14 ), which is an underdeveloped region in terms of medical resources and economic level. Therefore, investigating the rehabilitation status and burden of children with ASD is urgent in these regions, and the aim of this study was to focus on this issue.…”
Section: Introductionmentioning
confidence: 99%